Remote Implementation Of Laboratory Works - Modern Approach ﻿ - Bychkov, O.C. (Journal of Information Technologies in Education (ITE), 2009)
The question of providing the remote access to implementation of laboratory works is examined. Creation of such system requires realization of such functions: simulation of laboratory equipment, start of virtual laboratory works, remote connecting to the operating laboratory equipment.